Answers

2014-07-12T15:47:25+08:00
Just substitute the details to the formula.
9x²-72=0 ; a=9, b=0, c=-72

x= -(0) √(0)²-4(9)(-72) / 2(9)
x=√2592 / 18
x=50.912 / 18
x≈ 2.828, -2.828

2x²+4x=3 ; a=2, b=4, c=-3
x= -(4)√(4)²- 4(2)(-3) / 2 (2)
x=-(4)√16+24 / 4
x=-(4)+ √40 / 4 ; x= -(4) - √40 /4
x=-4+ 6.325 / 4 ; x= -4-6.325/4
x=2.325/4  ; x= -10.325/4
x≈0.5813 ; x= -2.5813

PS : your formula is wrong. please review. :)

0
yeah my formula is wrong the correct formula is thank you
yeah my formula is wrong i forgot to write the positive and negative after the -b
welcome..:))